2010
DOI: 10.1111/j.1467-9566.2009.01219.x
|View full text |Cite
|
Sign up to set email alerts
|

A sociological approach to ageing, technology and health

Abstract: This special monograph issue builds on sociology of health and illness scholarship and expands the analytical lens to examine how old people, healthcare professionals, and technology designers create, use, and modify science and technology to negotiate and define health and illness. Far from passive consumers, elders are technogenarians, creatively utilising and adapting technological artefacts such as walking aids and medications to fit their needs. This publication adds theoretical and empirical depth to our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 16 publications
0
74
0
10
Order By: Relevance
“…Joyce and Loe (2010), for example, lay out how the biomedicalization and commodification of aging is being conducted with and through technologies, pointing out how "[. .…”
Section: Structural-institutional Theories: Technologies and Social Imentioning
confidence: 99%
“…Joyce and Loe (2010), for example, lay out how the biomedicalization and commodification of aging is being conducted with and through technologies, pointing out how "[. .…”
Section: Structural-institutional Theories: Technologies and Social Imentioning
confidence: 99%
“…A contenda foi descrita por todo tipo de cientistas sociais interessados nas importantes questões por ela suscitadas, como aquelas ligadas às formas de representar socialmente o envelhecimento e os velhos, ao papel desempenhado pela ciência e pela tecnologia na conformação da sociedade, às possíveis consequências de uma maior extensão da vida para a organização social e, finalmente, às possíveis causas culturais, por assim dizer, de uma aceitação tão ampla do conhecimento antienvelhecimento pelo público (Joyce, Loe, 2010;Lafontaine, 2009;Mykytyn, 2010;Neilson, 2006;Post, Binstock, 2004). Outro ponto de grande interesse era o trabalho de demarcação de fronteiras empreendido pelos envolvidos na querela: muito foi dito e feito no intuito de fixar limites claros entre a medicina antienvelhecimento e aqueles que a atacavam.…”
Section: A Guerra Ao Antienvelhecimento Nos Eua E No Brasilunclassified
“…When it comes to resourcefulness, older age is a particularly interesting phase of life because it is characterized by encountering challenges in daily activities due to diminishing physical and mental capabilities [40]. At the same time, research in science and technology studies shows how technologies designed for older people -an area of development referred to as gerontechnology -tend to be particularly closed to forms of situated reinterpretation and repurposing [1,36,52].…”
Section: Introductionmentioning
confidence: 99%
“…Instead, as Loe puts it, 'what lies before them is time, new family configurations and opportunities for reinvention' [46]. In spite of persistent prejudice of elderly as technologically less skilled, research has shown elders to creatively use and adapt artefacts and technologies in daily life [40].…”
Section: Introductionmentioning
confidence: 99%